Preparation of Chitin, Study of Physicochemical Properties and Biopesticide Activities - Rohyami, Yuli; Istiningrum, Reni Banowati (EKSAKTA: Journal of Sciences and Data Analysis, 2013)
Chitin was preparated from shrimp shells by chemically method. Preparation was carried out by deproteination shrimp shells powder < 150 mesh with 1 - 2 M NaOH, demineralization followed by reaction with 1.0 M HCl and depigmentation with (1 : 2 : 4, v/v) of chloroform : methanol : water. Physicochemical properties of chitin was determined from characterization of infrared spectra, ash value, loss on drying and total of nitrogen. Biopesticide activities of chitin was done to pest Bemisia tabaci at guava leaves with various concentration from 0.5 to 2.0 % chitin on 3 % v/v acetic acid. This study indicated that concentration of NaOH on deproteination process effected to its physicochemicals properties. Effectivity of 2 M NaOH on deproteination reaction was higher than 1 M NaOH . The degree of chitin deacetylation from 2 M NaOH was 13.61% and had lower molar ratio of total nitrogen. The degree of deacetylation of chitin from 1 M NaOH had lower and had higher molar ratio of total nitrogen. Physicochemicals properties of chitin quite an impact on its ability to reduce pest Bemisia tabaci. Biopesticide activity assay showed that treatment for 2 days on average mortality rate of 13.83%. Deacetylation of chitin which has a higher degree have a greater ability biopesticide with a mortality rate of up to 38.24%. This study the effect of deproteination process to biopesticide activities of chitin. Key Words : chitin, degree of deacetilation, molar ratio, biopesticide, Bemisia tabaci